ANALISIS IMPLEMENTASI SISTEM MANAJEMEN MUTU BERDASARKAN ISO 9001:2015 - Azhari, Akmala Zulfa; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2023)
BAZNAS (the National Board of Zakat of the Republic of Indonesia) of X City applies a quality management system based on ISO 9001:2015 as its commitment to improve the administration quality of ZIS (zakat, infaq, and sadaqah) fund and DSKL (other religious social funds). The efforts of meeting the standard are aimed at increasing the trust of both muzakki and mustahik and carrying out an integrated information documenting process. The objective of this research is to analyze and identify the application, benefit, and obstacles of the ISO 9001:2015-based quality management system in BAZNAS of X City. The data of this qualitative case study was harvested from interviews and documentation. The results of the analysis demonstrate that BAZNAS of X City has applied the ten clauses of ISO 9001:2015 standard requirements. The implementation of ISO 9001:2015 has benefited the institution by enabling the acquisition of quality standards in delivering products and services to the customers, the ease in data tracing, and the minimization of risks. However, the implementation of ISO 9001:2015 is still hampered by the low human resource quantity and quality, which hinders the documentation process and the implementation of the said quality management system.